2013
DOI: 10.1007/s00181-013-0745-y
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality between Chinese regions: newfound harmony or continued discord?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…For instance, Ho and Li () investigated the stochastic properties of output per capita across the Chinese provinces for the period 1984 to 2003 and observed significant evidence of output divergence across the provinces. Similar evidence was obtained by Lyhagen and Rickne () for half of the Chinese cities by using the nonlinear trend functions in the vector error correction model (VECM) over the period 1952 to 2007.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…For instance, Ho and Li () investigated the stochastic properties of output per capita across the Chinese provinces for the period 1984 to 2003 and observed significant evidence of output divergence across the provinces. Similar evidence was obtained by Lyhagen and Rickne () for half of the Chinese cities by using the nonlinear trend functions in the vector error correction model (VECM) over the period 1952 to 2007.…”
Section: Introductionsupporting
confidence: 79%
“…Indeed, it is important to investigate the convergence clustering of the Chinese provinces with regards to economic indicators. One of the stylized facts in the literature is that the income inequality in the Chinese provinces has increased (divergence across provinces) since 1979 owing to the significant institutional reform in 1979 (Cheong & Wu, , ; Ho & Li, ; Knight, ; Lau, ; Lyhagen & Rickne, ). For instance, Ho and Li () investigated the stochastic properties of output per capita across the Chinese provinces for the period 1984 to 2003 and observed significant evidence of output divergence across the provinces.…”
Section: Introductionmentioning
confidence: 99%
“…The Relationship between Inequality, Bi-Polarization, Equity, and Urban Sustainability Equity has been a fundamental issue for human society and a major concern of governments worldwide [63]. Indeed, equity is an important factor to promote sustainable development, which can enhance the resilience of the economy [64], promote social harmony and stability [65], as well as protect environment [66] and biodiversity [67]. Furthermore, residents living in more equitable regions have better health and a longer life expectancy [68,69].…”
Section: The Relationship Between Urban Infrastructure and Urban Sustmentioning
confidence: 99%
“…The distribution of GDP per capita has fluctuated over the period since the beginning of reforms in 1978, with the coefficient of variation falling steadily over two decades from the late 1970s until the late 1990s, when it began to rise so that by 2004 it had returned to the level of the mid-1980s, after which it declined steadily to the end of the decade. 2 A recent paper by Lemoine et al (2014) confirms the observed recent decline in inequality and relates it to the growing convergence in manufacturing although another paper, Lyhagen and Rickne (2014), reports mixed evidence, with roughly half the possible provincepairs showing convergence and the remainder divergence.…”
Section: Introductionmentioning
confidence: 99%